Penerapan Tax Planning Dalam Upaya Meningkatkan Efisiensi Pembayaran Beban Pajak Pada Cv. Iqbal Perkasa - Muhammadinah Muhammadinah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2015)
The aims of this research are to analyze and explore the application of taxplanning to push up the efficiency of CV. Iqbal Perkasa’s tax burden payment, whichis specialized in construction project services in Banyuasin. By using thequantitative analysis method, this research finds out that calculation on tax burdenpayment is more costly, so it was reduced net profit after tax that gained by CV.Iqbal Perkasa. But, after using tax planning by maximized fiscal cost with gross upmethod, it could minimize tax liability. The research finds with a better taxplanning in line with a gross up method, CV Iqbal Perkasa stated a betterperformance on tax efficiency by minimization of tax liability in current and futuretax periodsKey words: Tax Planning, Efficiency and Tax Liability